INDEKS RISIKO BENCANA PARIWISATA DAN KLASTER KABUPATEN KOTA JAWA BARAT BERBASIS DATA WISATA 2020–2024: TOURISM DISASTER RISK INDEX AND CLUSTERING OF WEST JAVA REGENCIES AND CITIES BASED ON TOURISM DATA (2020–2024) - Ucu Nugraha; Sri Titi Handayani; Hernalom Sitorus; Bobi Kurniawan S; Adam Mukharil Bachtiar; Ednawati Rainarli; Hanhan Maulana (Rabit : Jurnal Teknologi dan Sistem Informasi Univrab, 2026)
West Java Province is one of Indonesia’s leading tourism destinations and, at the same time, a region with a high incidence of disasters. However, available disaster risk information such as the Indonesian Disaster Risk Index and the West Java Provincial Disaster Risk Assessment remains broad in scope and has not explicitly integrated the tourism dimension. This study aims to develop a Tourism Disaster Risk Index at the regency/municipality level in West Java Province by utilizing data on the number of disaster events, the number of disaster victims during the 2020–2024 period, and the number of tourism destination objects, while also clustering regions to construct a disaster-based typology of tourism risk. The methods include: (1) aggregating five-year disaster event and victim data by regency/municipality; (2) calculating the total number of tourism destination objects (natural, cultural, and man-made); (3) applying min–max normalization to produce partial indices for events, victims, and tourism destination objects; (4) constructing a composite Tourism Disaster Risk Index using weights of 0.4:0.4:0.2, in which hazard (events) and impact (victims) are deliberately assigned greater weights than tourism exposure as a conceptual decision aligned with disaster risk frameworks that prioritize life safety and physical damage; and (5) applying the K-Means algorithm (k = 3) to perform clustering based on the partial indices. The results show that the Tourism Disaster Risk Index (0–100 scale) ranges from 0.76 to 56.70, with a mean of 12.27 and a median of 6.90. A total of 25 regencies/municipalities fall into the low tourism risk category, while Bogor Regency and Cianjur Regency are in the moderate category. The clustering yields three clusters: cluster 1 comprises 21 regencies/municipalities with relatively low tourism risk; cluster 2 includes five regencies (Bogor, Bandung, Garut, Majalengka, and Pangandaran) characterized by moderate risk and a high concentration of destinations; and cluster 3 consists solely of Cianjur Regency as an outlier with exceptionally high disaster impacts. These findings provide a quantitative foundation as well as a prototype decision-support tool for local governments and stakeholders to prioritize resources and design interventions for disaster-resilient tourism development in West Java Province.